Clinic variation in glycaemic control for children with Type 1 diabetes in England and Wales: a population‐based, multilevel analysis. Issue 12 (31st August 2017) - Charalampopoulos, D.; Amin, R.; Warner, J. T.; Muniz‐Terrera, G.; Mazarello Paes, V.; Viner, R. M.; Stephenson, T.
Abstract: Aim: To understand the scope for improving children's glycaemic outcomes by reducing variation between clinics and examine the role of insulin regimen and clinic characteristics. Methods: Cross‐sectional analysis of 2012–2013 National Paediatric Diabetes Audit data from 21 773 children aged < 19 years with Type 1 diabetes cared for at 176 clinics organized into 11 regional diabetes networks in England and Wales. Variation in HbA1c was explored by multilevel models with a random effect for clinic. The impact of clinic context was quantified by computing the per cent of total variation in HbA1c which occurs between clinics (intraclass correlation coefficient; ICC). Results: Overall, 69 of the 176 diabetes clinics (39%) had a glycaemic performance that differed significantly from the national average after adjusting for patient case‐mix with respect to age, gender, diabetes duration, deprivation and ethnicity. However, differences between clinics accounted for 4.7% of the total variation in HbA1c . Inclusion of within‐clinic HbA1c standard deviation led to a substantial reduction in ICC to 2.4%. Insulin regimen, clinic volume and diabetes networks had a small or moderate impact on ICC. Conclusions: Differences between diabetes clinics accounted for only a small portion of the total variation in glycaemic control because most of the variation was within clinics. This implies that national glycaemic improvements might best be achieved not only by targeting poor centres but also by shifting the whole distribution of clinics to higher levels of quality. What's new?: This is the first population‐based study to quantify the impact of clinic context on glycaemic control in children with Type 1 diabetes in the UK using robust multilevel techniques. Overall, children who attended clinics with less variable glycaemic results had better glycaemic control. There were noticeable differences in HbA1c between diabetes clinics over and above individual characteristics. However, glycaemic control varied more within rather than between clinics and interventions targeting only poor clinics would fail to capture most children in need. Glycaemic improvements might best be achieved by not only reducing clinic variation, but also shifting the whole distribution of clinics to higher levels of quality.